2004
DOI: 10.1017/s0021932004006534
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status as a Risk Factor for Hiv Infection in Women in East, Central and Southern Africa: A Systematic Review

Abstract: This is a critical, systematic review of the relationship between socioeconomic status (SES) and HIV infection in women in Southern, Central and Eastern Africa. In light of the interest in micro-credit programmes and other HIV prevention interventions structured to empower women through increasing women's access to funds and education, this review examines the epidemiological and public health literature, which ascertains the association between low SES using different measurements of SES and risk of HIV infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(137 citation statements)
references
References 93 publications
9
127
0
1
Order By: Relevance
“…These studies were selected on the basis of 'type of study design; representativeness of study sample of country or regional population; completeness of follow-up for cohort studies; measurement of SES and measurement of outcome indicators or other indicators of sexual risk-taking' (Wojcicki, 2005, pp.5-6). Fifteen of these studies found no association between SES and HIV infection; 12 found an association between low SES and HIV infection; and 1 yielded mixed results (Wojcicki, 2005).…”
Section: Others)mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies were selected on the basis of 'type of study design; representativeness of study sample of country or regional population; completeness of follow-up for cohort studies; measurement of SES and measurement of outcome indicators or other indicators of sexual risk-taking' (Wojcicki, 2005, pp.5-6). Fifteen of these studies found no association between SES and HIV infection; 12 found an association between low SES and HIV infection; and 1 yielded mixed results (Wojcicki, 2005).…”
Section: Others)mentioning
confidence: 99%
“…That poverty and disease are inextricably linked is widely accepted, as is evident from the mounting literature on the subject (Barnett & Whiteside, 2002;Booysen, 2004;Wojcicki, 2005), as well as public debate on the issue (The Chatroom, SABC 1, 25 July 2004). Recent research has tended to extend this link to HIV/AIDS.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] Women globally, and black African women in particular, tend to fall into the lower socio economic stratum and are disproportionately affected by HIV. [15] There is also evidence that the association between HIV, SES and gender varies depending on income inequality in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Where income per capita is high and intracountry inequalities are high, HIV risk increases. [14] With regard to employment status, black women were more likely than black men to be unemployed and looking for work. Full-time employment rates were higher for men than for women.…”
Section: Discussionmentioning
confidence: 99%
“…This kind of despair and total lack of hope of improving wellbeing at household, drive this woman and several other into ''problem''. Contradictory evidences exist with regard to HIV vulnerability at the level of households and communities (Wojciki 2005;Giraldo, 1997). Early studies had demonstrated positive correlations between household economic resources, education, and HIV infection, as the epidemic progressed; however currently, this relationship is somehow slightly changing.…”
Section: Decomposition Changes In Povertymentioning
confidence: 99%